The perceived impact of the In Trust Agreements on CGIAR germplasm availability: An assessment of Bioversity International’s institutional activities - Gotor, Elisabetta; Caracciolo, Francesco; Watts, J. (Elsevier, 2010)
This study assesses the generation and consequences of the In-Trust Agreements (ITAs) that established the legal status of the CGIAR germplasm as freely available for the benefit of humanity under the auspices of FAO. The analysis looks at the history of the ITAs and focuses on the role of Bioversity International in research and other activities in influencing, facilitating and enabling the ITA negotiations. Results confirm the central role of Bioversity and policy research in the negotiations process. Concepts developed during the ITA negotiations contributed towards subsequent multilateral negotiations that eventually culminated in the International Treaty on Plant Genetic Resources. (taken from publisher web site)